The DNA of the Democratic South Africa: Ancestral Maps, Family Trees, Genealogical Fictions. - Bystrom, Kerry (Journal of Southern African Studies, 2009)
This article focuses on the discourse of popular science - and particularly that of genetics and evolution - as it has been used in the democratic South Africa to develop and articulate a shared 'African' national identity. Analysing speeches by politicians and academics, as well as sites of popular culture ranging from television shows to the Maropeng centre at the Cradle of Humankind, I explore how a new 'evolutionary family narrative', in which all humans are understood to have an African 'mother', has been harnessed in an attempt to guarantee 'belonging' to citizens of all races. I further show how this specific genetic family narrative is one of a larger network of 'genealogical fictions' that have been fabricated and produced in part for the purpose of redefining the national community in the post-apartheid era, and which tend to reiterate the basic tropes of nineteenth- and early twentieth-century nation-building projects in the new millennium. Finally, I analyse two novels - Zoë Wicomb's David's Story and Nadine Gordimer's Get a Life - that debate the continuing usefulness of such genealogical fictions in the work of building a contemporary democratic nationalism.